Impact of monitor unit optimization in volumetric modulated arc therapy planning for nasopharyngeal carcinoma - Zeng, Huaqu; Li, Zhen; Chen, Zongyou; Tang, Shukui; Lin, Qifu; Zhong, Minzhi; Wen, Zunbei (PloS one, 2025)
To evaluate the impact of monitor units (MUs) optimization on volumetric modulated arc therapy (VMAT) plan for nasopharyngeal carcinoma (NPC). Twenty-one NPC patients were retrospectively analyzed. Dual-arc VMAT plan were designed using photon optimization algorithms without the monitor unit objective (MUO) tool, denoted as the base plan. Each base plan was re-optimized with the MUO tool with the Maximum MU parameter set to 30% of the base plans' total MUs and Strength parameters set to 50, 80, and 100, generating plans S50, S80, and S100. Target and organ-at-risk (OAR) dose distributions, MUs, beam delivery time, and gamma passing rates were compared between re-optimized and base plans. Statistical analysis was performed using SPSS 17.0 (paired t-tests; significance: P < 0.05). Plan S100 reduced target PCTV2 D98% by >4% (relative to the base plan) in four patients. Plan S80 reduced target PGTV and PGTVnd Dmax and target PCTV2 D98% for >3% but <4% in two patients, while other target dose parameters changed by <2%. Compared to the base plan, all re-optimized plans increased the brainstem Dmax (P < 0.05), though the maximum increase was < 1.5%. Plan S50 reduced both parotid glands D50% and Dmean (P < 0.001), while plan S80 reduced both parotids Dmean and the left parotid D50% (P < 0.001). Conversely, S100 increased both parotids D50% and Dmean and the spinal cord Dmax (P < 0.05). Plan S80 and S100 increased the thyroid V40 (P < 0.05). MU reductions averaged 5.1% (S50), 21.4% (S80), and 30.9% (S100), with consistent beam delivery times (~2.5 minutes). Gamma passing rates improved sequentially from the base plan to S50, S80, and S100. MU optimization in NPC VMAT planning effectively reduces MUs and enhances delivery accuracy (improved gamma passing rates). While target coverage and OAR sparing were generally maintained, higher MUO strengths (e.g., S100) may necessitate careful consideration of dosimetric trade-offs. Moderate MUO settings (e.g., S80) offer a favorable balance between MU reduction and plan fidelity.